Dampak Tax Holiday Apple Inc. di Indonesia terhadap Pertumbuhan Ekonomi Global - Yanti, Wa Ode Irma Yanti; Bahari, Muhammad Naufal Rizan; Tamaela , Meyrill Debora G.; Siswatiningrum, Etik (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2025)
This research examines the impact of the tax holiday policy given to Apple Inc. in Indonesia on global economic growth. This research uses a descriptive qualitative method to explore and understand the phenomena that occur as a result of the policy. Data is collected through analyzing related documents, such as Apple's financial statements, government reports, journal articles, and media news. The results show that the tax holiday has the potential to attract foreign investment, increase employment, and accelerate technology transfer to Indonesia. However, there are also concerns about the loss of tax revenue that the state should receive and the impact on local business competition. In addition, this study found that the policy may create unfairness for domestic companies that do not receive similar incentives. Thus, while tax holidays can boost short-term economic growth, their long-term impact on economic structure and social equity needs to be taken seriously. This research is expected to provide insights for policymakers in formulating more inclusive and sustainable investment strategies in the future. Keywords: FDI, Global Economic Growth, MNCs, Apple Inc.